2012
DOI: 10.3892/ijmm.2012.1150
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin has antifibrotic effects in scleroderma fibroblasts via downregulation of Dnmt1 and upregulation of Fli1

Abstract: Systemic sclerosis (SSc) is characterized by fibrosis of the skin and internal organs. The present study was undertaken to examine the effects of ciprofloxacin, a fluoroquinolone antibiotic implicated in matrix remodeling, on dermal and lung fibroblasts obtained from SSc patients. Dermal and lung fibroblasts from SSc patients and healthy subjects were treated with ciprofloxacin. Western blotting was used to analyze protein levels and RT-PCR was used to measure mRNA expression. The pharmacologic inhibitor UO126… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Metalloproteases and their inhibitors are intertwined and form a basis for a metabolic matrix tissue stability that may be interrupted pharmacologically. This theory is in line with previous observations revealing antifibrotic activity 8 and decreased collagen-1 protein expression with fluoroquinolones. 9 The enigmatic puzzle of the progression of some aortic events may alarmingly be iatrogenic, and the clinician may wisely consider a prudent use of fluoroquinolones in patients with aortic dilatation.…”
supporting
confidence: 93%
“…Metalloproteases and their inhibitors are intertwined and form a basis for a metabolic matrix tissue stability that may be interrupted pharmacologically. This theory is in line with previous observations revealing antifibrotic activity 8 and decreased collagen-1 protein expression with fluoroquinolones. 9 The enigmatic puzzle of the progression of some aortic events may alarmingly be iatrogenic, and the clinician may wisely consider a prudent use of fluoroquinolones in patients with aortic dilatation.…”
supporting
confidence: 93%
“…They showed that addition of the DNMT inhibitor 2-deoxy-5-azacytidine (5-aza) and HDAC inhibitor trichostatin A (TSA) decreased collagen content in SSc fibroblasts, possibly through normalizing the hypermethylated and hypoacetylated promoter region of the collagen suppressor gene Friend leukemia integration 1 (FLI1), hence increasing Fli-1 expression. The impact of DNA methylation on FLI1 expression was further confirmed by Bujor et al [92]. They showed that the antifibrotic effect of ciprofloxacin, a broad spectrum antibiotic, in SSc dermal fibroblasts and SSc-interstitial lung disease lung fibroblasts stemmed from downregulation of DNMT1 and upregulation of FLI1.…”
Section: Epigenetic Impact In Ssc Pathogenesismentioning
confidence: 77%
“…Also, multiple existing drugs that might be repurposed to treat fibrosis [134] such as the peroxisome proliferator-activated receptor-γ agonists, rosiglitazone [135], statins [136,137], fluoroquinolone antibiotics such as ciprofloxacin [138,139], and thrombin inhibitors such as dabigatran [140], are being considered. However, given that the pathogenic mechanisms of fibrotic diseases in SSc are quite complex with multiple and often redundant pathways, blocking a single molecule or pathway will likely not be sufficient.…”
Section: Novel Ssc Therapies Currently Under Evaluationmentioning
confidence: 99%